2009
DOI: 10.2337/db08-1365
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Depletion of grem1 Attenuates Diabetic Kidney Disease

Abstract: OBJECTIVEGremlin (grem1) is an antagonist of the bone morphogenetic protein family that plays a key role in limb bud development and kidney formation. There is a growing appreciation that altered grem1 expression may regulate the homeostatic constraints on damage responses in diseases such as diabetic nephropathy.RESEARCH DESIGN AND METHODSHere we explored whether knockout mice heterozygous for grem1 gene deletion (grem1+/−) exhibit protection from the progression of diabetic kidney disease in a streptozotocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 32 publications
4
65
0
1
Order By: Relevance
“…Grem1−/− embryos were readily isolated from grem1+/− crosses, although at lower than expected Mendelian frequencies (data not shown). These fibroblasts provided a robust model in which to test proliferative responses in the total absence of Grem1, as opposed to previous experiments examining cells with reduced Grem1 expression [20,22]. We have previously shown that Grem1 expression is detected in MEFs isolated from E13.5 embryos [22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Grem1−/− embryos were readily isolated from grem1+/− crosses, although at lower than expected Mendelian frequencies (data not shown). These fibroblasts provided a robust model in which to test proliferative responses in the total absence of Grem1, as opposed to previous experiments examining cells with reduced Grem1 expression [20,22]. We have previously shown that Grem1 expression is detected in MEFs isolated from E13.5 embryos [22].…”
Section: Resultsmentioning
confidence: 99%
“…1. Generation of mouse embryo fibroblasts (MEFs).MEFs were generated from E13.5 embryos of grem1+/− crosses and genomic DNA isolated as described in [22]. A. PCR reactions to detect the wild-type grem1 allele or recombinant LacZ allele were performed to identify wild-type, grem1+/− or grem1−/− cells.…”
Section: Grem1mentioning
confidence: 99%
See 2 more Smart Citations
“…Increased Gremlin1 expression has been identified in fibrosis associated with kidney, lung, heart and liver disease [10,11]. Targeting Gremlin1 by gene deletion or shRNA knockdown reduced the severity of kidney disease in mouse models of diabetic nephropathy (DN) [12,13]. A genetic variant of Gremlin1 is associated with increased risk of diabetic nephropathy [14].…”
mentioning
confidence: 99%